The effectiveness of the nursing intervention program on feeling of burden and coping among caregivers of children with epilepsy - El-malky, Maaly; Mohsen, Magda; Amer, Hemat (International Journal of Advanced Nursing Studies, 2016)
Epilepsy is one of the most common pediatric neurological disorders, which have negative psychological, emotional, and physical consequences of providing care. Nursing intervention is a key element of managing these patients and their families in order to reduce feelings of burden and enhancing coping among caregivers. Aim: To evaluate the effectiveness of nursing intervention on a feeling of burden and coping among caregivers of children with epilepsy. Design: A quasi-experimental design (one group pretest-posttest design) was used to achieve the aim of the study. Setting: The study was conducted at the outpatient clinic at the health insurance institute in Shebin El-Kom district, Menoufia Governorate. Subject: A convenience sample of 80 caregivers was used. Tool: I- A constructed interviewing questionnaire was developed by researchers to assess socio demographic data, medical history and family caregiver’s knowledge, practices and opinions regarding child with epilepsy. II- Modified version of the Zarit burden interviewing questionnaire to assess feeling of burden. III- Coping Health Inventory for Parents to assess coping patterns of care giver’s. The Results: the main finding of this study illustrated that, there were statistical significance differences regarding caregivers’ knowledge and practices. Reduction of the feeling of burden and improvement of coping patterns after nursing intervention than before. There was a negative correlation between caregiver’s knowledge, practice and feeling of burden and there was a positive correlation between (KPO) and coping among caregivers. The majority of the studied caregivers were mothers (76%) with mean age score37.21±5.22, more than half were secondary education, and the majority (75%) was not working. Conclusion: Nursing intervention was effective in improving caregiver’s knowledge, practices and opinions, feeling of burden and raising coping abilities for caregivers of children with epilepsy. Recommendation: additional nursing strategies are needed around the time of the diagnosis with longitudinal assessment and follow up for both caregivers and their children.